Effect of Vandetanib Treatment on Cystic Changes in the Liver following Metastasis from Medullary Thyroid Carcinoma - Ai Matsui; Soji Toda; Daisuke Murayama; Hiroyuki Iwasaki (Case Reports in Endocrinology)
A number of causes are responsible for the development of cystic lesions in the liver. However, metastasis is a rare cause, and cystic metastasis from medullary thyroid carcinoma has not yet been reported. A 46-year-old Japanese man presented to our hospital with a mass in the left side of his neck. Neck and thyroid ultrasonography revealed a thyroid tumor with calcification and enlarged cervical lymph nodes. He had a family history of medullary thyroid cancer. Computed tomography revealed a tumor in the thyroid and multiple cysts in the liver. Total thyroidectomy with modified neck and upper mediastinum dissections were performed. After surgery, vandetanib treatment was initiated owing to tumor progression; following this, the liver cysts increased in size, abdominal distension appeared, and serum liver enzyme levels were found to be elevated. Percutaneous liver cyst puncture was performed to reduce abdominal distension; however, it was ineffective. The liver enzyme levels improved after replacing vandetanib with lenvatinib treatment. The liver cysts in this case were indicated to be associated with medullary thyroid carcinoma.